Enhancing magnetoresistive features of iron-substituted La0·8Sr0·2MnO3 ceramic manganites - Karadavut, Samed; Denbri, Fatih; Terzioğlu, Cabir; Öztürk, Özberk; Altıntaş, Sevgi Polat (Elsevier BV, 2022)
The influence of iron content on the structural, microstructural, magnetic, and electrical-transport features of the ceramic perovskite manganites of the form La0.8Sr0.2Mn1-xFexO3 (x=0.0, 0.05, 0.1, and 0.2) was investigated. A single phase of rhombohedral-distorted structure with an R c space group was confirmed for all synthesized ceramic samples. The microstructures of the manganite ceramics were improved by iron substitution. The magnetic and electrical-transport studies show that samples with x=0.0, 0.05, and 0.1 display phase transitions from ferromagnetic to paramagnetic state and metallic to insulating one with increasing temperature. The phase transition temperatures, i.e., Curie temperature, TC, and the resistance transition temperature TMI, are found to be lowered with the increase in the Fe concentration. The temperature coefficient of resistance (TCR) value for the x=0.0 sample is obtained similar to 2.16% K-1 and slightly decreased to similar to 1.55% K-1 with a 5% Fe substituted sample. As x rise to 0.1, we obtain the maximum TCR value of similar to 8.23% K-1. At the same time, the maximum magnetoresistance is obtained as 48.1% at 233 K for the x=0.1 sample. One of the most important findings in this paper is that Fe substitution is very useful for improving magneto-electrical features of the La0.8Sr0.2MnO3 ceramics. Moreover, to better understand the temperature dependence of the electrical resistivity data, the experimental findings were fitted to the equations of several models.
Keywords: Magnetoresistance; Magnetic-Properties; Transition Element; Magnetization; TCR; Phase Transition